Diffractive technospaces : a feminist approach to the mediations of space and representation - Timeto, Federica (Ashgate, 2015)
The entanglements of information and materiality in our media environment, that new information and communication technologies make increasingly mobile and locative, changes the mediations between space and society. The fluidity and continual reworking of the boundaries of contemporary technospaces - the sociotechnical environments in which humans and machines relate and intersect - is key to the production and consumption of contemporary technologies. Theoretical analyses of communication and space have tended to engage in the representation of such changes without interrogating the representational instruments used at a broader methodological level. Articulating a non-representational perspective on knowledge production and artistic practices, combined with an analysis of space, this book offers a new performative and relational re-turn to representation in contemporary technospaces. The radically materialist, posthumanist and performative position from which this situated aesthetics of technospaces is elaborated, aligns this book not only with non-representational theory, but also with the theories of material feminism, feminist geography, situated epistemologies, science and technology studies, actor-network theory, performance studies and new media studies.--from publisher.